Asymmetric diaphragm and preparation method thereof
By applying cast film liquid containing different high-temperature aramid concentrations on both sides of the base film of the lithium battery separator, and carrying out two-stage solidification bath treatment, the existing separator poor compatibility and insufficient adhesion are solved. , the heat resistance and bonding performance of the diaphragm are improved, and the bonding performance requirements of different electrode materials are met.
Patent Information
- Application Number
- CN202411280829.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The slurry of the existing lithium battery separator has poor compatibility with the separator, which makes the slurry easy to fall off, reducing the heat resistance of the separator and the service life of the lithium battery. At the same time, it is difficult to achieve the difference between the adhesive force between the positive and negative electrodes in the prior art. , cannot meet the bonding performance requirements of different electrode materials.
By adopting an asymmetric diaphragm preparation method, the first coating and the second coating are formed by coating the cast film liquid A and the cast film liquid B on both sides of the base film, and performing two-stage solidification bath treatment. The high-temperature resistant aramid content in the layer is different, and the second coating has a high content to ensure the heat resistance and bonding properties of the membrane.
The different requirements of the bonding force between the separator and the positive and negative electrodes are achieved, the heat resistance and battery safety performance of the separator are improved, and the energy waste and production costs are reduced, so as to prepare the required hot press bonding force for different electrode materials. Diaphragm.
Smart Images

Figure CN118801041B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an asymmetric diaphragm and a preparation method thereof, belonging to the technical field of lithium battery materials. Background Art
[0002] In the structure of lithium batteries, the diaphragm is one of the key internal components. The diaphragm is located between the positive electrode and the negative electrode. Its main function is to separate the positive and negative active materials to prevent the two electrodes from short-circuiting due to contact, while allowing the rapid transport of charged ions. In order to improve the heat resistance of the diaphragm, a layer of slurry needs to be applied to the diaphragm to improve the safety performance of lithium batteries. However, at present, the compatibility between the slurry and the diaphragm in the relevant prior art is poor, which makes the slurry easy to fall off the diaphragm, resulting in a weakening of the heat resistance of the diaphragm product, which in turn affects the service life of the lithium battery.
[0003] With the development of battery technology, battery production efficiency has improved. On the basis of traditional winding and lamination processes, some battery companies have also developed more advanced thermal composite lamination processes. Usually, the lamination process or thermal composite lamination process requires a certain degree of adhesion between the diaphragm and the positive and negative electrodes to reduce the gap between the diaphragm and the positive and negative electrodes during the battery charging and discharging process, and improve the battery charging and discharging performance. The method currently used by diaphragm companies is to coat PVDF on the base film. For example: Chinese patent application CN105552284A discloses a composite coated lithium-ion battery diaphragm and a preparation method thereof, wherein a PVDF coating is coated on the battery diaphragm, and the PVDF coating used is obtained by coating and drying an aqueous PVDF slurry. In addition, Chinese patent application CN104993089A discloses an aramid-coated lithium-ion battery diaphragm and a preparation method thereof, wherein the diaphragm is composed of a lithium-ion battery base film and a coating on one or both sides of the base film, wherein the coating is obtained by coating, soaking, and drying an aramid slurry, and the aramid slurry is composed of an aramid fiber dissolving liquid, an emulsifier solution, and a polymer adhesive. Although these related technologies can effectively improve the adhesion between the diaphragm and the electrode piece, they cannot achieve different adhesion between the diaphragm and the positive and negative electrodes. For the positive and negative electrode materials and battery processes of the battery, there are differences in the adhesion between the positive and negative electrodes and the diaphragm, so it is necessary to achieve different adhesion between the positive and negative electrodes on both sides of the diaphragm, and for different electrode materials, the adhesion performance requirements for the diaphragm are different.
[0004] At present, commercialized PVDF diaphragms are mainly PVDF coated on polyolefin diaphragms mainly composed of polyethylene and polypropylene, including water-based coating and oil-based coating. On the one hand, the bonding force between the positive and negative electrodes and the diaphragm is the same, and the bonding condition of the diaphragm cannot be regulated. On the other hand, there are safety hazards caused by poor heat resistance. Furthermore, it is generally necessary to coat twice to achieve adhesion on both sides of the diaphragm, which causes high costs due to energy waste. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an asymmetric diaphragm and a method for preparing the same. The asymmetric diaphragm can not only meet the different bonding forces with the positive and negative electrodes, but also improve the heat resistance of the diaphragm, thereby improving the safety performance of the battery, and can also meet the high bonding requirements. In addition, simultaneous double-sided coating can greatly reduce energy waste and thus reduce costs, and the asymmetric diaphragm preparation method can specifically prepare a diaphragm with the required hot pressing bonding force.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing an asymmetric diaphragm, the preparation method comprising:
[0007] S1, high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, and after being mixed evenly, a casting solution A is obtained;
[0008] The high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, and after being mixed evenly, a casting solution B is obtained;
[0009] S2, coating the casting liquid A and the casting liquid B on both sides of the base film to form a first coating layer and a second coating layer, and then performing a two-stage coagulation bath treatment, and finally washing and drying to obtain an asymmetric diaphragm;
[0010] The mass content of the high temperature resistant aromatic polyamide in the first coating and the second coating is different;
[0011] The high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide; the weight average molecular weight of the meta-aramid is 150,000-250,000, and the weight average molecular weight of the PVDF is 400,000-800,000;
[0012] The weight average molecular weight of the para-aramid is 40,000-80,000; the weight average molecular weight of the heterocyclic aramid is 200,000-400,000; and the weight average molecular weight of the polyamide-imide is 100,000-300,000.
[0013] Furthermore, the thickness of the first coating layer is 0.5-4.0 μm, and the thickness of the second coating layer is 0.5-4.0 μm.
[0014] Furthermore, the mass content of the high-temperature resistant aromatic polyamide in the first coating is 0-20%; the mass content of the high-temperature resistant aromatic polyamide in the second coating is 50-75%.
[0015] Furthermore, the difference in weight average molecular weight between the PVDF and the meta-aramid is not less than 250,000;
[0016] The difference in weight average molecular weight between the PVDF and the para-aramid is not less than 400,000;
[0017] The difference in weight average molecular weight between the PVDF and the heterocyclic aramid is not less than 250,000;
[0018] The difference in weight average molecular weight between the PVDF and the polyamide-imide is not less than 350,000.
[0019] Furthermore, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 2-10wt%, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B is 2-10wt%;
[0020] The slurry viscosity of the casting liquid A and the casting liquid B is 30-10000 mpa·s.
[0021] Furthermore, a pore former is added or not added to the casting liquid A and the casting liquid B, the mass content of the pore former in the casting liquid A is 0%-10%, and the mass content of the pore former in the casting liquid B is 0%-10%.
[0022] Furthermore, the coagulation bath is a mixed solution of a polar solvent and water, the mass concentration of the polar solvent in the first coagulation bath is 30%-60%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-20%, and the temperature of the second coagulation bath is 20-50°C.
[0023] Furthermore, the concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
[0024] Furthermore, the polar solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
[0025] The present invention also discloses an asymmetric diaphragm, which is prepared by the preparation method of the present invention; the hot pressing bonding force of the first coating is 10-30N / m 2 ; Hot pressing bonding force of the second coating 1-12N / m 2 ;
[0026] The rupture temperature of the asymmetric diaphragm is not less than 220° C.; and the air permeability is not greater than 400s / 100cc.
[0027] The beneficial effects of the present invention are:
[0028] The preparation method of the present invention can meet the different requirements of the bonding force between the diaphragm and the positive electrode and the negative electrode, better match the battery processing technology, and improve the battery cycle capacity retention rate. In addition, the asymmetric diaphragm preparation method of the present invention can specifically prepare a diaphragm with the required hot pressing bonding force. In actual production, a diaphragm that meets the requirements can be directly prepared according to the downstream application requirements, thereby greatly reducing the workload of exploring experimental conditions.
[0029] The preparation method of the present invention selects a high-temperature resistant aromatic polyamide polymer solution and PVDF of suitable molecular weight to prepare the diaphragm coating, and combines the setting of a two-stage coagulation bath to make the diaphragm have good heat resistance and good bonding performance. Because in the two-stage coagulation molding process, in the first-stage coagulation bath, the high-temperature resistant aromatic polyamide is first pre-solidified and formed, and PVDF is just filled in the surface pores of the pre-solidified high-temperature resistant aromatic polyamide; in the second-stage coagulation bath, PVDF and the unformed high-temperature resistant aromatic polyamide are completely solidified; this process can keep as much PVDF as possible on the surface of the diaphragm, so that the diaphragm can have good heat resistance and bonding performance at the same time. It can effectively solve the problem of poor adhesion of the diaphragm caused by the simultaneous molding of a mixed solution of a high-temperature resistant polymer and an adhesive polymer PVDF. At the same time, the setting of the coagulation bath conditions can make the diaphragm coating have good flatness and strength performance, and have uniform pores, and ultimately improve the comprehensive application performance of the diaphragm.
[0030] At present, the diaphragm production processes that can meet the requirements of heat resistance and adhesion of diaphragms on the market mostly prepare heat-resistant coatings first, and then apply secondary adhesive coatings after winding. In the preparation method of the present invention, double-sided coating can be applied simultaneously, which can meet the requirements of heat resistance and adhesion of diaphragms and reduce production costs.
[0031] The asymmetric diaphragm prepared by the preparation method of the present invention can increase the diaphragm rupture temperature, improve the diaphragm heat resistance, and improve the battery safety performance. The air permeability of the asymmetric structure coated diaphragm is ≤400s / 100cc, the rupture temperature is ≥220℃, the rupture temperature of the meta-aramid coated diaphragm can even be as high as 260℃, and the rupture temperature of the para-aramid coated diaphragm can be as high as 400℃ (equipment limit) without rupture. The asymmetric diaphragm can delay the heat spread time of the battery, reduce the thermal runaway temperature, and improve the battery safety performance.
[0032] In the preparation method of the present invention, the components on both sides of the substrate are of the same type, the raw material composition is simple, and the coating on both sides can be applied simultaneously. The operation is simple, the coating thickness is controllable, and the bonding force between the separator and the positive and negative electrodes is controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the structure of the asymmetric diaphragm of the present invention;
[0034] Figure 2 This is a SEM image of the first coating surface of the asymmetric coating diaphragm in Example 1;
[0035] Figure 3 This is the SEM image of the second coating surface of the asymmetric coating membrane in Example 1. DETAILED DESCRIPTION
[0036] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0038] A method for preparing an asymmetric diaphragm, the preparation method comprising:
[0039] S1, high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, mechanically stirred at 20-60°C for 0.5-4.0h, and after mixing evenly, a casting solution A is obtained;
[0040] The high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, mechanically stirred at 20-60° C. for 0.5-4.0 h, and after being mixed evenly, a casting solution B is obtained;
[0041] S2, coating the casting liquid A and the casting liquid B on both sides of the base film to form a first coating layer and a second coating layer, and then performing a two-stage coagulation bath treatment, and finally washing and drying to obtain an asymmetric diaphragm;
[0042] The mass content of the high temperature resistant aromatic polyamide in the first coating and the second coating is different;
[0043] The high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide; the weight average molecular weight of the meta-aramid is 170,000-230,000, and the weight average molecular weight of the PVDF is 500,000-800,000.
[0044] Specifically, the porosity of the first coating is 30-70%, and the porosity of the second coating is 30-70%;
[0045] The thickness of the first coating layer is 0.5-4.0 μm, and the thickness of the second coating layer is 0.5-4.0 μm. The structure of the diaphragm is as follows Figure 1 shown.
[0046] Specifically, the mass content of the high temperature resistant aromatic polyamide in the first coating is 0-20%; the mass content of the high temperature resistant aromatic polyamide in the second coating is 50-75%;
[0047] The hot pressing bonding force of the first coating is 10-30N / m 2 ; Hot pressing bonding force of the second coating 1-12N / m 2 .
[0048] Specifically, the difference in weight average molecular weight between the PVDF and the meta-aramid is not less than 250,000;
[0049] The difference in weight average molecular weight between the PVDF and the para-aramid is not less than 400,000;
[0050] The difference in weight average molecular weight between the PVDF and the heterocyclic aramid is not less than 250,000;
[0051] The difference in weight average molecular weight between the PVDF and the polyamide-imide is not less than 350,000.
[0052] Specifically, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 2-10wt%, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B is 2-10wt%;
[0053] The slurry viscosity of the casting liquid A and the casting liquid B is 30-5000 mpa·s.
[0054] Specifically, the mass content of the pore-forming agent in the casting solution A is 2%-10%, and the mass content of the pore-forming agent in the casting solution B is 2%-10%.
[0055] More specifically, the pore-forming agent is PVP, PEG, etc., but is not limited to these. The pore-forming agent used in the embodiment of the present invention is PVP K30, PVP K90, PEG 200, PEG 400, PEG 800, PEG 1000 or PEG 2000.
[0056] Specifically, the coagulation bath is an aqueous solution of a polar solvent, the mass concentration of the polar solvent in the first coagulation bath is 30%-60%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-20%, and the temperature of the second coagulation bath is 20-50°C.
[0057] Specifically, the concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
[0058] Specifically, the polar solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.
[0059] More specifically, the base film used in the embodiment of the present invention is a 7 μm PE film.
[0060] Example 1
[0061] (1) Meta-aramid polymer solution (weight average molecular weight of 210,000) and PVDF (weight average molecular weight of 600,000) were mixed in DMAc at a certain solid content, and mechanically stirred at 20°C for 0.5 h. After complete dissolution, casting solution A was obtained; the slurry viscosity of casting solution A was 20 mPa·s, and the mass fraction of high temperature resistant aromatic polyamide in the casting solution A was 2 wt%. The mass ratio of PVDF / meta-aramid was 4 / 1.
[0062] (2) Meta-aramid polymer solution (weight average molecular weight of 210,000) and PVDF (weight average molecular weight of 600,000) were mixed in DMAc at a certain solid content, pore former PVP K30 was added, and mechanical stirring was performed at 20°C for 0.5 h. After complete dissolution, casting solution B was obtained; the mass content of the pore former in the casting solution B was 10%, the slurry viscosity of the casting solution B was 5000 mpa·s, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 10wt%. The mass ratio of meta-aramid / PVDF was 1 / 1.
[0063] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40° C. after washing for 30 seconds, and then roll up after drying;
[0064] The first coagulation bath is a DMAc aqueous solution with a mass concentration of 30% and a temperature of 30°C.
[0065] The second coagulation bath is an aqueous solution of DMAc with a mass concentration of 5% and a temperature of 20°C;
[0066] The thickness of the first coating layer was 0.5 μm, and the thickness of the second coating layer was 4.0 μm.
[0067] The mass content of high temperature resistant aromatic polyamide in the first coating is 20%; the mass content of PVDF in the first coating is 80%;
[0068] The mass content of high temperature resistant aromatic polyamide in the second coating is 50%; the mass content of PVDF in the second coating is 50%.
[0069] Among them, the SEM image of the first coating surface is as follows Figure 2 As shown, the SEM image of the second coating surface is as follows Figure 3 As shown, from Figure 2 and Figure 3 It can be seen that the pore structure of the first coating is mostly smaller pores, and the second coating is sponge-like pores. The advantages of this structure are: the small pores of the first coating make the diaphragm surface more PVDF, and the effective bonding cotton that can be provided during the hot pressing process with the pole piece is larger; the sponge-like pores of the second coating have a high porosity, which can increase the ion migration rate and improve the battery cycle performance.
[0070] Example 2
[0071] (1) PVDF (weight average molecular weight of 600,000) was mixed with DMAc at a certain solid content, and a pore former PVP K30 was added. The mixture was mechanically stirred at 20°C for 0.5 h, and a casting solution A was obtained after the mixture was completely dissolved. The mass content of the pore former in the casting solution A was 10%, the slurry viscosity of the casting solution A was 120 mpa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A was 0wt%, and the mass fraction of PVDF was 10%.
[0072] (2) Meta-aramid polymer solution (weight average molecular weight of 210,000) and PVDF (weight average molecular weight of 600,000) were mixed in DMAc at a certain solid content, pore former PVP K30 was added, and mechanical stirring was performed at 20°C for 0.5 h. After complete dissolution, casting solution B was obtained; the mass content of the pore former in the casting solution B was 0%, the slurry viscosity of the casting solution B was 60 mpa·s, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 2wt%. The mass ratio of meta-aramid / PVDF was 3 / 1.
[0073] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40° C. after washing for 30 seconds, and then roll up after drying;
[0074] The first coagulation bath is a DMAc aqueous solution with a mass concentration of 60% and a temperature of 60°C.
[0075] The second coagulation bath is an aqueous solution of DMAc with a mass concentration of 20% and a temperature of 50°C;
[0076] The thickness of the first coating layer is 4.0 μm; the thickness of the second coating layer is 0.5 μm.
[0077] The mass content of high temperature resistant aromatic polyamide in the first coating is 0%; the mass content of PVDF in the first coating is 100%;
[0078] The mass content of high temperature resistant aromatic polyamide in the second coating is 75%; the mass content of PVDF in the second coating is 25%.
[0079] Example 3
[0080] (1) Meta-aramid polymer solution (weight average molecular weight of 150,000) and PVDF (weight average molecular weight of 400,000) were mixed in DMAc at a certain solid content, pore former PVP K30 was added, and mechanical stirring was performed at 20°C for 0.5 h. After complete dissolution, casting solution A was obtained; the mass content of the pore former in the casting solution A was 5%, the slurry viscosity of the casting solution A was 45 mpa·s, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A was 5wt%. The mass ratio of PVDF / meta-aramid was 9 / 1.
[0081] (2) Meta-aramid polymer solution (weight average molecular weight of 150,000) and PVDF (weight average molecular weight of 400,000) were mixed in DMAc at a certain solid content, pore former PVP K30 was added, and mechanical stirring was performed at 20°C for 0.5 h. After complete dissolution, casting solution B was obtained; the mass content of the pore former in the casting solution B was 5%, the slurry viscosity of the casting solution B was 80 mpa·s, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 5wt%. The mass ratio of meta-aramid / PVDF was 1.86 / 1.
[0082] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40° C. after washing for 30 seconds, and then roll up after drying;
[0083] The first coagulation bath is a DMAc aqueous solution with a mass concentration of 40% and a temperature of 40°C.
[0084] The second coagulation bath is an aqueous solution of DMAc with a mass concentration of 10% and a temperature of 30°C;
[0085] The thickness of the first coating is 1.0 μm; the thickness of the second coating is 2.0 μm.
[0086] The mass content of high temperature resistant aromatic polyamide in the first coating is 10%; the mass content of PVDF in the first coating is 90%;
[0087] The mass content of high temperature resistant aromatic polyamide in the second coating is 65%; the mass content of PVDF in the second coating is 35%.
[0088] Example 4
[0089] (1) A meta-aramid polymer solution (weight average molecular weight of 250,000) and PVDF (weight average molecular weight of 800,000) were mixed in DMAc at a certain solid content, a pore former PVP K30 was added, and mechanical stirring was performed at 40°C for 2 hours. After complete dissolution, a casting solution A was obtained; the mass content of the pore former in the casting solution A was 5%, the slurry viscosity of the casting solution A was 110 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A was 5wt%, and the mass ratio of PVDF / meta-aramid was 9 / 1.
[0090] (2) The meta-aramid polymer solution (weight average molecular weight of 250,000) and PVDF (weight average molecular weight of 800,000) were mixed in DMAc at a certain solid content, and the pore former PVP K30 was added. The mixture was mechanically stirred at 40°C for 2 hours, and the casting solution B was obtained after the solution was completely dissolved. The mass content of the pore former in the casting solution B was 5%, the slurry viscosity of the casting solution B was 2500mpa·s, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 5wt%. The mass ratio of meta-aramid / PVDF was 1.86 / 1
[0091] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 50° C. after washing for 60 seconds, and then roll up after drying;
[0092] The first coagulation bath is a DMAc aqueous solution with a mass concentration of 40% and a temperature of 30°C.
[0093] The second coagulation bath is an aqueous solution of DMAc with a mass concentration of 20% and a temperature of 20°C;
[0094] The thickness of the first coating layer is 1.0 μm; the thickness of the second coating layer is 1.0 μm.
[0095] The mass content of high temperature resistant aromatic polyamide in the first coating is 10%; the mass content of PVDF in the first coating is 90%;
[0096] The mass content of high temperature resistant aromatic polyamide in the second coating is 65%; the mass content of PVDF in the second coating is 35%.
[0097] Example 5
[0098] (1) A para-aramid polymer solution (weight average molecular weight of 40,000) and PVDF (weight average molecular weight of 600,000) are mixed in NMP at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 40° C. for 2 h. After complete dissolution, a casting solution A is obtained; the mass content of the pore former in the casting solution A is 10%, the slurry viscosity of the casting solution A is 125 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 2 wt%, and the mass ratio of PVDF / para-aramid is 19 / 1.
[0099] (2) A para-aramid polymer solution (weight average molecular weight of 40,000) and PVDF (weight average molecular weight of 600,000) were mixed in NMP at a certain solid content, a pore former PVP K30 was added, and mechanical stirring was performed at 40°C for 2 hours. After complete dissolution, a casting solution B was obtained; the mass content of the pore former in the casting solution B was 10%, the slurry viscosity of the casting solution B was 85 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 2 wt%, and the mass ratio of para-aramid to PVDF was 1 / 1.
[0100] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40° C. after washing for 30 seconds, and then roll up after drying;
[0101] The first coagulation bath is an aqueous solution of NMP with a mass concentration of 40% and a temperature of 60°C.
[0102] The second coagulation bath is an aqueous solution of NMP with a mass concentration of 10% and a temperature of 40°C;
[0103] The thickness of the first coating layer is 2.0 μm; the thickness of the second coating layer is 2.0 μm.
[0104] The mass content of high temperature resistant aromatic polyamide in the first coating is 5%; the mass content of PVDF in the first coating is 95%;
[0105] The mass content of high temperature resistant aromatic polyamide in the second coating is 50%; the mass content of PVDF in the second coating is 50%.
[0106] Example 6
[0107] (1) A para-aramid polymer solution (weight average molecular weight of 80,000) and PVDF (weight average molecular weight of 750,000) are mixed in NMP at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 40° C. for 2 h. After complete dissolution, a casting solution A is obtained; the mass content of the pore former in the casting solution A is 5%, the slurry viscosity of the casting solution A is 8800 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 10 wt%, and the mass ratio of PVDF / para-aramid is 4 / 1.
[0108] (2) A para-aramid polymer solution (weight average molecular weight of 80,000) and PVDF (weight average molecular weight of 750,000) were mixed in NMP at a certain solid content, a pore former PVP K30 was added, and mechanical stirring was performed at 40°C for 2 hours. After complete dissolution, a casting solution B was obtained; the mass content of the pore former in the casting solution B was 5%, the slurry viscosity of the casting solution B was 9775 mpa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 10 wt%, and the mass ratio of para-aramid to PVDF was 3 / 1.
[0109] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40° C. after washing for 30 seconds, and then roll up after drying;
[0110] The first coagulation bath is an aqueous solution of NMP with a mass concentration of 60% and a temperature of 30°C.
[0111] The second coagulation bath is an aqueous solution of NMP with a mass concentration of 20% and a temperature of 20°C;
[0112] The thickness of the first coating layer is 4.0 μm; the thickness of the second coating layer is 4.0 μm.
[0113] The mass content of high temperature resistant aromatic polyamide in the first coating is 20%; the mass content of PVDF in the first coating is 80%;
[0114] The mass content of high temperature resistant aromatic polyamide in the second coating is 75%; the mass content of PVDF in the second coating is 25%.
[0115] Example 7
[0116] (1) Polyamide-imide (weight average molecular weight of 100,000) and PVDF (weight average molecular weight of 800,000) are mixed in N-methylpyrrolidone at a certain solid content, and a pore former PVP K30 is added. The mixture is mechanically stirred at 60° C. for 4 h, and a casting liquid A is obtained after the mixture is completely dissolved. The mass content of the pore former in the casting liquid A is 10%, the slurry viscosity of the casting liquid A is 3000 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting liquid A is 10 wt%, and the mass ratio of PVDF / polyamide-imide is 19 / 1.
[0117] (2) Polyamide-imide (weight average molecular weight of 100,000) and PVDF (weight average molecular weight of 800,000) were mixed in N-methylpyrrolidone at a certain solid content, and a pore-forming agent PVP K30 was added. The mixture was mechanically stirred at 60° C. for 4 h, and a casting solution B was obtained after the mixture was completely dissolved. The mass content of the pore-forming agent in the casting solution B was 10%, the slurry viscosity of the casting solution B was 4000 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B was 10 wt%, and the mass ratio of polyamide-imide / PVDF was 1.5 / 1.
[0118] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 60° C. after washing for 60 seconds, and then roll up after drying;
[0119] The first coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 50% and a temperature of 40°C.
[0120] The second coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 20% and a temperature of 20°C;
[0121] The thickness of the first coating layer is 4.0 μm; the thickness of the second coating layer is 4.0 μm.
[0122] The mass content of high temperature resistant aromatic polyamide in the first coating is 5%; the mass content of PVDF in the first coating is 95%;
[0123] The mass content of high temperature resistant aromatic polyamide in the second coating is 60%; the mass content of PVDF in the second coating is 40%.
[0124] Example 8
[0125] (1) Polyamide-imide (weight average molecular weight of 300,000) and PVDF (weight average molecular weight of 800,000) are mixed in N,N-dimethylacetamide at a certain solid content, and a pore former PVP K30 is added. The mixture is mechanically stirred at 60° C. for 4 h, and a casting liquid A is obtained after the mixture is completely dissolved. The mass content of the pore former in the casting liquid A is 10%, the slurry viscosity of the casting liquid A is 284 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting liquid A is 2 wt%, and the mass ratio of PVDF / polyamide-imide is 4 / 1.
[0126] (2) Polyamide-imide (weight average molecular weight of 300,000) and PVDF (weight average molecular weight of 800,000) were mixed in N,N-dimethylacetamide at a certain solid content, and a pore former PVP K30 was added. The mixture was mechanically stirred at 60° C. for 4 h, and a casting liquid B was obtained after the mixture was completely dissolved. The mass content of the pore former in the casting liquid B was 10%, the slurry viscosity of the casting liquid B was 5600 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting liquid B was 10 wt%, and the mass ratio of polyamide-imide / PVDF was 1 / 1.
[0127] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 60° C. after washing for 60 seconds, and then roll up after drying;
[0128] The first coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 30% and a temperature of 30°C.
[0129] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 5% and a temperature of 50°C;
[0130] The thickness of the first coating layer is 2.0 μm; the thickness of the second coating layer is 2.0 μm.
[0131] The mass content of high temperature resistant aromatic polyamide in the first coating is 20%; the mass content of PVDF in the first coating is 80%;
[0132] The mass content of high temperature resistant aromatic polyamide in the second coating is 50%; the mass content of PVDF in the second coating is 50%.
[0133] Example 9
[0134] (1) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 200,000) and PVDF (weight average molecular weight of 700,000) are mixed in N-methylpyrrolidone at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 30° C. for 1 hour. After complete dissolution, a casting solution A is obtained; the mass content of the pore former in the casting solution A is 3%, the slurry viscosity of the casting solution A is 180 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 6wt%, and the mass ratio of PVDF / heterocyclic aramid is 4 / 1.
[0135] (2) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 200,000) and PVDF (weight average molecular weight of 700,000) are mixed in N-methylpyrrolidone at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 30° C. for 1 hour. After complete dissolution, a casting solution B is obtained; the mass content of the pore former in the casting solution B is 3%, the slurry viscosity of the casting solution B is 350 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B is 6 wt%, and the mass ratio of heterocyclic aramid to PVDF is 1 / 1.
[0136] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first stage coagulation bath and the second stage coagulation bath in sequence, and then enter the drying oven at 60° C. after washing for 60 seconds, and then roll up after drying;
[0137] The first coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 35% and a temperature of 60°C.
[0138] The second coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 10% and a temperature of 45°C;
[0139] The thickness of the first coating layer is 2.0 μm; the thickness of the second coating layer is 2.0 μm.
[0140] The mass content of high temperature resistant aromatic polyamide in the first coating is 20%; the mass content of PVDF in the first coating is 80%;
[0141] The mass content of high temperature resistant aromatic polyamide in the second coating is 50%; the mass content of PVDF in the second coating is 50%.
[0142] Example 10
[0143] (1) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 400,000) and PVDF (with a weight average molecular weight of 800,000) are mixed in N,N-dimethylformamide at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 30° C. for 1 hour. After complete dissolution, a casting solution A is obtained; the mass content of the pore former in the casting solution A is 3%, the slurry viscosity of the casting solution A is 240 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 6wt%, and the mass ratio of PVDF / heterocyclic aramid is 4 / 1.
[0144] (2) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 400,000) and PVDF (with a weight average molecular weight of 800,000) are mixed in N,N-dimethylformamide at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 30° C. for 1 hour. After complete dissolution, a casting solution B is obtained; the mass content of the pore former in the casting solution B is 3%, the slurry viscosity of the casting solution B is 410 mPa·s, the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B is 6 wt%, and the mass ratio of heterocyclic aramid to PVDF is 1 / 1.
[0145] (3) The casting liquid A and the casting liquid B obtained in steps (1) and (2) are simultaneously coated on both sides of the base film through a micro-concave roller, and then enter the first stage coagulation bath and the second stage coagulation bath in sequence, and then enter the drying oven at 60° C. after washing for 60 seconds, and then roll up after drying;
[0146] The first coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 30% and a temperature of 50°C.
[0147] The second coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 5% and a temperature of 35°C;
[0148] The thickness of the first coating layer is 3.0 μm; the thickness of the second coating layer is 4.0 μm.
[0149] The mass content of high temperature resistant aromatic polyamide in the first coating is 20%; the mass content of PVDF in the first coating is 80%;
[0150] The mass content of high temperature resistant aromatic polyamide in the second coating is 50%; the mass content of PVDF in the second coating is 50%.
[0151] Comparative Example 1
[0152] The diaphragm was prepared by the same method as in Example 1, except that only PVDF was contained in the casting solution A and the casting solution B, and no high temperature resistant aromatic polyamide was added.
[0153] Comparative Example 2
[0154] The diaphragm was prepared by the same method as in Example 1, except that in Comparative Example 2, the meta-aramid polymer solution was replaced with meta-aramid of the same molecular weight.
[0155] Comparative Example 3
[0156] The same method as in Example 1 was used to prepare the diaphragm, except that only one coagulation bath treatment was performed. The conditions for the one-stage coagulation bath in Comparative Example 3 were as follows: the coagulation bath was an aqueous solution of DMAc with a mass concentration of 15% and a coagulation bath temperature of 40°C.
[0157] Comparative Example 4
[0158] The diaphragm was prepared by the same method as in Example 1, except that the concentration of the second coagulation bath was increased so that the concentration difference between the first coagulation bath and the second coagulation bath was less than 20%. In this comparative example 4, the mass concentration of the second coagulation bath was 20%.
[0159] Comparative Example 5
[0160] The diaphragm was prepared by the same method as in Example 1, except that the temperature of the second coagulation bath was increased so that the temperature difference between the first coagulation bath and the second coagulation bath was less than 10° C. In Comparative Example 5, the temperature of the second coagulation bath was 25° C.
[0161] Comparative Example 6
[0162] The diaphragm was prepared by the same method as in Example 1, except that the raw material PVDF was replaced. In this comparative example 6, the weight average molecular weight of the raw material PVDF was 400,000 (the difference in weight average molecular weight between PVDF and high temperature resistant aromatic polyamide in this comparative example 6 was 190,000).
[0163] The performance of the diaphragms prepared in the above examples and comparative examples was tested, and the specific results are shown in Table 1 below.
[0164] The detection methods involved are:
[0165] The hot-pressing bonding force testing method comprises the following steps:
[0166] (1) Fold the basement membrane in half along the midline and place it between two sheets of silicone oil paper;
[0167] (2) Turn on the plastic sealing heat press (U-H6330T) and set the parameters: temperature to 120°C and speed to 2700 mm / min;
[0168] (3) Place the diaphragm sample into the laminator from one side, take it out from the other side, and lay it flat on the cutting pad;
[0169] (4) Use a 15 mm cutter to cut a coated diaphragm sample with a width of 15.0 mm and a length of >18 cm;
[0170] (5) Turn on the switch of the electronic tensile testing machine and test the peel strength of the sample. For specific operations, refer to the provisions of 6.5.6 in T / CPPIA10-2021.
[0171] The test method for film rupture temperature is as follows: in accordance with GB / T 36800.1, the sample size is 8.0×4.0 mm in length and width, and the specific test method is as follows:
[0172] 1) Cut the sample into strips with a size of 8 × 4 mm in length × width in the MD and TD directions respectively, and fix them in the fixture of the instrument;
[0173] 2) Select a thin film probe and a quartz platform, place the sample on the sample platform, set the test parameters: preload force is 0.03N, high-purity nitrogen flow rate is 40mL / min, temperature range is 50-300℃, rate is 5℃ / min, and start measurement;
[0174] 3) The measured value is taken as the test result.
[0175] Table 1 Diaphragm performance test
[0176]
[0177] From the above data, it can be seen that the diaphragms prepared by the preparation method of the present invention in Examples 1 to 10 can meet the different hot pressing bonding forces of the positive and negative electrodes, the air permeability value is ≤400s / 100cc, and the membrane rupture temperature is ≥220°C.
[0178] From the data comparison of Example 1 and Comparative Example 1, it can be seen that after double-sided coating of PVDF, the hot pressing bonding strength between the diaphragm and the positive and negative electrodes is very large and the values are the same, which cannot meet the battery process with different bonding strengths of the positive and negative electrodes, and the membrane rupture temperature is very low, which makes it difficult to meet the battery safety requirements.
[0179] From the data comparison of Example 1 and Comparative Example 2, it can be seen that after replacing the meta-aramid polymer liquid with aramid fiber, the hot pressing bonding strength of the diaphragm coating will be reduced, the air permeability value will be increased and the membrane rupture temperature will be reduced. This is because when the aramid fiber is redissolved, there will be a microcrystalline structure in which the fiber is not completely dissolved, which affects the diaphragm's properties such as bonding strength, air permeability and membrane rupture temperature.
[0180] From the data comparison of Example 1 and Comparative Example 3, it can be seen that when only one-stage coagulation bath is adopted, high-temperature resistant aromatic polyamide and PVDF are precipitated simultaneously, which is not conducive to the formation of PVDF on the surface of the diaphragm, resulting in a decrease in adhesion, and the diaphragm obtained by the one-stage coagulation bath has a lower porosity and poorer air permeability.
[0181] From the data comparison of Example 1 and Comparative Examples 4 and 5, it can be seen that reducing the concentration difference or temperature difference between the primary coagulation bath and the secondary coagulation bath will reduce the hot pressing bonding strength to varying degrees. The effect of temperature on the hot pressing bonding strength of the diaphragm coating is more obvious than the concentration. This shows that the effect of temperature on the molding speed of high temperature resistant polymers and PVDF is higher than the effect of concentration.
[0182] From the data comparison between Example 1 and Comparative Example 6, it can be seen that the smaller the difference between the molecular weights of the high-temperature resistant aromatic polyamide and PVDF, the more it will affect the molding process of the high-temperature resistant aromatic polyamide and PVDF in the coagulation bath. The smaller the difference, the closer the molding speeds are, and PVDF and aramid will be molded on the coating surface at the same time.
[0183] Application Examples 1-10 and Comparative Application Examples 1-6
[0184] The diaphragm obtained in the above example is assembled into a 4Ah 811 system ternary lithium battery using a lamination process.
[0185] The batteries assembled with the separators of the above embodiments 1-10 and comparative examples 1-6 correspond to application examples 1-10 and comparative application examples 1-6, respectively.
[0186] Application Comparative Example 7
[0187] The battery was assembled using the same method as in Application Example 1, except that the separator was replaced with a commercially available 7 μm PE-based film.
[0188] Application Comparative Example 8
[0189] The battery was assembled using the same method as in Application Example 1, except that the separator was replaced with a commercially available (1+2+7+2+1) μm PE / ceramic / PVDF coating membrane, where 2 is the ceramic coating thickness, 1 is the coating thickness of the water-based roller-coated PVDF, and 7 is the PE base membrane thickness.
[0190] The batteries of the above application examples and application comparison examples were subjected to performance tests, and the specific test results are shown in Table 2 below.
[0191] Table 2 Battery performance test results
[0192]
[0193] From the above table data, it can be seen that the diaphragm prepared by the preparation method of the present invention in the battery of application examples 1-10 has an improved capacity retention rate after 100 cycles compared with the PE base film and the PE / ceramic / PVDF coating film, which is above 90%, and can effectively improve the battery cycle life. In the Arc (accelerating calorimeter) test, application comparison example 1 and application comparison example 8 have no high temperature resistant coating layer, and the measured Arc temperatures are 698°C and 739°C, respectively. The Arc temperature of application comparison example 8 with a high temperature resistant ceramic coating is reduced to 620°C, and the Arc temperature of application examples 1-7 with a high temperature resistant aromatic polyamide coating is reduced to below 500°C, among which the high temperature resistant aromatic polyamide in application examples 5-6 and application examples 9-10 respectively adopts para-aramid and aromatic III with better heat resistance, and the Arc temperature of the battery prepared by the diaphragm is also the lowest, which is 412°C and 434°C, respectively. It can be seen from this that the diaphragm prepared by the preparation method of the present invention has good application performance in the battery.
[0194] From the data comparison between Application Example 1 and Application Comparative Example 1, it can be seen that the capacity retention rate of Application Comparative Example 1 is reduced, and the Arc temperature is 253°C higher. Without high-temperature resistant aromatic polyamide, the safety of the battery made of the diaphragm is greatly reduced.
[0195] From the data comparison between Application Example 1 and Comparative Example 2, it can be seen that the DCR value of Comparative Example 2 has increased. This is because the incompletely dissolved aramid microcrystalline structure increases the internal resistance of the battery, thereby affecting the cycle life and reducing its capacity retention rate.
[0196] From the data comparison between Application Example 1 and Application Comparative Example 3, it can be seen that the DCR value of Application Comparative Example 3 is improved compared with that of Application Example 1. This is because the one-stage coagulation bath regulates the pore structure of the aromatic polyamide and PVDF coating during the molding process, resulting in low porosity and high permeability, and the pore structure is not uniform as regulated by the two-stage coagulation bath, which ultimately leads to a decrease in the capacity retention rate.
[0197] From the data comparison of Application Example 1 and Application Comparison Example 4 and Application Comparison Example 5, it can be seen that: the concentration difference between the primary coagulation bath and the secondary coagulation bath in Application Comparison Example 4 is less than 20%, and the temperature difference between the primary coagulation bath and the secondary coagulation bath in Application Comparison Example 5 is less than 10°C. The difference in concentration and temperature between the two-stage coagulation baths is too small, which makes the difference in the order of high-temperature resistant aromatic polyamide and PVDF in the molding process small, and the distribution of PVDF and aromatic polyamide is relatively uniform, which reduces the adhesion between the coating and the electrode, thereby affecting the ionic conductivity and DCR value, and affecting the capacity retention rate. However, from the data, the influence of temperature is greater than that of concentration, which is consistent with the performance data such as the hot pressing adhesion of the diaphragm in Table 1.
[0198] From the data comparison between Application Example 1 and Application Comparative Example 6, it can be seen that the difference in molecular weight between aromatic polyamide and PVDF has a smaller impact on the difference in safety performance, but a greater impact on battery performance. This is mainly because the large difference in molecular weight is more conducive to the sequence of aromatic polyamide and PVDF in the molding process, so that more PVDF is molded on the coating surface, which is beneficial to increase the amount of effective PVDF, thereby improving the adhesion of the coating. Therefore, the capacity retention rate of Application Comparative Example 6 is reduced, but the Arc temperature does not have a great impact.
[0199] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0200] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing an asymmetric diaphragm, characterized in that: The preparation method is: S1, high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, and after being mixed evenly, a casting solution A is obtained; The high temperature resistant aromatic polyamide polymer solution and PVDF are mixed in a polar solvent, and after being mixed evenly, a casting solution B is obtained; S2, coating the casting liquid A and the casting liquid B on both sides of the base film to form a first coating layer and a second coating layer, and then performing a two-stage coagulation bath treatment, and finally washing and drying to obtain an asymmetric diaphragm; The mass content of the high temperature resistant aromatic polyamide in the first coating and the second coating is different; The high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide; The weight average molecular weight of the meta-aramid is 150,000-250,000, and the weight average molecular weight of the PVDF is 400,000-800,000; The weight average molecular weight of the para-aramid is 40,000-80,000; the weight average molecular weight of the heterocyclic aramid is 200,000-400,000; the weight average molecular weight of the polyamide-imide is 100,000-300,000; The mass content of the high temperature resistant aromatic polyamide in the first coating is 0-20%; the mass content of the high temperature resistant aromatic polyamide in the second coating is 50-75%; The coagulation bath is a mixed solution of a polar solvent and water, the mass concentration of the polar solvent in the first coagulation bath is 30%-60%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-20%, and the temperature of the second coagulation bath is 20-50°C; The concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
2. The method for preparing an asymmetric diaphragm according to claim 1, characterized in that: The thickness of the first coating layer is 0.5-4.0 μm, and the thickness of the second coating layer is 0.5-4.0 μm.
3. The method for preparing an asymmetric diaphragm according to claim 1, characterized in that: The difference in weight average molecular weight between the PVDF and the meta-aramid is not less than 250,000; The difference in weight average molecular weight between the PVDF and the para-aramid is not less than 400,000; The difference in weight average molecular weight between the PVDF and the heterocyclic aramid is not less than 250,000; The difference in weight average molecular weight between the PVDF and the polyamide-imide is not less than 350,000.
4. The method for preparing an asymmetric diaphragm according to claim 1, characterized in that: The mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 2-10wt%, and the mass fraction of the high temperature resistant aromatic polyamide in the casting solution B is 2-10wt%; The slurry viscosity of the casting liquid A and the casting liquid B is 30-10000 mpa·s.
5. The method for preparing an asymmetric diaphragm according to claim 1, characterized in that: A pore former is added or not added to the casting liquid A and the casting liquid B. The mass content of the pore former in the casting liquid A is 0%-10%, and the mass content of the pore former in the casting liquid B is 0%-10%.
6. A method for preparing an asymmetric diaphragm according to any one of claims 1 to 5, characterized in that: The polar solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
7. An asymmetric diaphragm, characterized in that: The asymmetric diaphragm is prepared according to the preparation method according to any one of claims 1 to 6; The hot pressing bonding force of the first coating is 10-30N / m 2 ; Hot pressing bonding force of the second coating 1-12N / m 2 ; The rupture temperature of the asymmetric diaphragm is not less than 220° C.; and the air permeability is not greater than 400s / 100cc.
Citation Information
Patent Citations
Aramid coated lithium ion battery diaphragm and preparation method thereof
CN104993089A
Composite coating lithium-ion battery separator and preparation method thereof
CN105552284A
Meta-aramid and oil PDVF composite coating diaphragm and preparation method thereof
CN112490581A
Polymer mixed slurry coated diaphragm and preparation method thereof
CN113540687A